2000
DOI: 10.1097/00007632-200003010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Results Between Conventional and Computer-Assisted Pedicle Screw Installation in the Thoracic, Lumbar, and Sacral Spine

Abstract: Computer assistance can decrease the incidence of incorrectly positioned pedicle screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
239
3
28

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 421 publications
(280 citation statements)
references
References 27 publications
10
239
3
28
Order By: Relevance
“…At review, 48 papers were excluded as they did not meet the inclusion criteria (Table 1). Thus, 23 publications [5,6,8,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were analysed in this paper (Table 2; 2 randomised controlled trials, 12 case-control studies and 9 case series). Three studies were in German language and remaining 20 studies were in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At review, 48 papers were excluded as they did not meet the inclusion criteria (Table 1). Thus, 23 publications [5,6,8,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were analysed in this paper (Table 2; 2 randomised controlled trials, 12 case-control studies and 9 case series). Three studies were in German language and remaining 20 studies were in English.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [12,13,19,24,26,30] reported follow-up period ranging from 15 to 34 months, while one study followed the patients to clinical and radiological bony fusion [16], but none reported on rate of fusion achieved.…”
Section: Fusion Ratementioning
confidence: 99%
“…Considering the narrow margin of error [2,26] in pedicular screw placement, we considered those screws within the safe zone which were displaced by \2 mm on medial side and by \4 mm on lateral side. In previous studies, rate of pedicle-wall perforation varied between 1.5 and 43% [2,8,11,18,20,22,29,30,36,37]. Most studies have shown usually rates of misplacement between 28 and 43% and only a few studies have shown rates less than 5% [2].…”
Section: Discussionmentioning
confidence: 98%
“…So, accurate and safe placement of screw within the pedicle is a crucial step during the surgery. Various methods such as free hand technique, Penfield outside-in technique, under C-arm control, computer assisted navigational surgery and stereotectic surgery, etc., to put the pedicle screw have been described in the literature [20,22,29]. The use of intra-operative fluoroscopy for placement of pedicle screws has resulted in prolonged fluro time and radiation exposure to the surgical personnel and patient [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation